A meta-analytic review of emotional intelligence in gifted individuals: A multilevel analysis - Ogurlu, U. (Personality and Individual Differences, 2020)
Some research has examined emotional intelligence among gifted individuals, but these individual studies have provided mixed results. The present meta-analysis aimed to clarify the nature of the relationship between emotional intelligence and giftedness. Hedge's unbiased g was used as the effect size metric, and a 3-level multilevel meta-analytic approach was applied, due to the dependency among the effect sizes obtained from the same study. The analyses used 81 effect sizes, from 17 published studies, and indicated that there was a significant difference between gifted and non-gifted participants in terms of emotional intelligence in favor of gifted individuals (g = 0.120, p = .023, 95% CI [0.031, 0.208]). The moderator analyses revealed that gifted individuals tended to be more emotionally intelligent when emotional intelligence is measured based on ability, but not trait models. The implications and limitations of the findings are discussed.